2017
DOI: 10.1016/j.steroids.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Age- and menopause-related differences in subcutaneous adipose tissue estrogen receptor mRNA expression

Abstract: Objectives Changes in estrogen receptor (ER) expression likely underlie differential metabolic effects of estrogen in pre-and postmenopausal women. The aim of the current study was to determine whether ER gene expression in abdominal and femoral subcutaneous adipose tissue (SAT) was associated with age, menopause, or regional adiposity. Methods We studied pre-and post-menopausal (n=23 and 22, respectively; age 35–65 y) normal weight (mean±SD; BMI 23.7±2.5 kg/m2) women with similar total fat mass. Abdominal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 25 publications
3
22
2
2
Order By: Relevance
“…In general, men showed greater accumulation of visceral fat and greater age‐related decreases in leg fat than women; however, this difference decreased when older males were compared with postmenopausal females . A retrospective cohort study by Park et al, which enrolled premenopausal and postmenopausal normal weight women with similar total fat mass, highlighted that increased age was associated with lower ERα and a decreased balance of ERα to ERβ in abdominal and femoral subcutaneous adipose tissue . Combined with the results of this study, we might speculate a possible pathophysiological mechanism to explain why premenopausal women seemed to be protected against cardiovascular morbidity and mortality in comparison with men of similar age or postmenopausal women…”
Section: Discussionsupporting
confidence: 72%
“…In general, men showed greater accumulation of visceral fat and greater age‐related decreases in leg fat than women; however, this difference decreased when older males were compared with postmenopausal females . A retrospective cohort study by Park et al, which enrolled premenopausal and postmenopausal normal weight women with similar total fat mass, highlighted that increased age was associated with lower ERα and a decreased balance of ERα to ERβ in abdominal and femoral subcutaneous adipose tissue . Combined with the results of this study, we might speculate a possible pathophysiological mechanism to explain why premenopausal women seemed to be protected against cardiovascular morbidity and mortality in comparison with men of similar age or postmenopausal women…”
Section: Discussionsupporting
confidence: 72%
“…These data suggest, that the ERs regulate VEGFA in an opposite way. It is known that the decline of E2 levels in postmenopausal women is associated with reductions of ESR1 expression, as well as there is a change in ESR1/ESR2 ratio such that there is more ESR2 relative to ESR1 45 . In addition, the postmenopausal period is characterized by increased visceral adiposity and enhanced metabolic risks associated with obesity 46 , which may reflect either the reductions in E2 and/or ESR1 expression, and their relative impact on VEGFA.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that there was an inverse link between age and gene expression for ERα and the ratio of ERα to ERβ in female abdominal subcutaneous fatty tissue [35]. Some researchers have found that the prevalence of obesity varies not only by age but also by income and educational levels [36,37].…”
Section: Characteristics Of Participantsmentioning
confidence: 99%